If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(5x + -8) + -4(8x + 3) = -68 Reorder the terms: 7(-8 + 5x) + -4(8x + 3) = -68 (-8 * 7 + 5x * 7) + -4(8x + 3) = -68 (-56 + 35x) + -4(8x + 3) = -68 Reorder the terms: -56 + 35x + -4(3 + 8x) = -68 -56 + 35x + (3 * -4 + 8x * -4) = -68 -56 + 35x + (-12 + -32x) = -68 Reorder the terms: -56 + -12 + 35x + -32x = -68 Combine like terms: -56 + -12 = -68 -68 + 35x + -32x = -68 Combine like terms: 35x + -32x = 3x -68 + 3x = -68 Add '68' to each side of the equation. -68 + 68 + 3x = -68 + 68 Combine like terms: -68 + 68 = 0 0 + 3x = -68 + 68 3x = -68 + 68 Combine like terms: -68 + 68 = 0 3x = 0 Solving 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '3'. x = 0 Simplifying x = 0
| 2x-4-3x+30=6 | | 5y+40=5y+40 | | 4x^2-6.25=0 | | f(x)=x^2+40 | | (5x+2)(6x-10)(x+20)=180 | | 5v-8=-53 | | 200-(-400)= | | J(u-w)=t | | X^2-14x-234=0 | | 6v(4v-8)= | | 70=.28*x | | 49b^2=256 | | 3x^2+10x+8=-2 | | 4[x-5]=-3[x-5] | | 3a+12b+15= | | 9[7-(7x-9)]+6x=0 | | -2x+24=0 | | 12x+-9+62+-3x+16x+2=180 | | 4x*2=49 | | 8(x-3)+5=8x+7 | | 3(2z-6)-4(3z+1)=5-2(2+1) | | 6x+3y+9x+y= | | 3n+4=8n-1 | | 4(2w+3)+2(3+w)= | | 4(w-6)=3(a+1) | | 7x+13=2x+8 | | -21+7y=9x | | 58-2+7=8x | | 3a+34b= | | 0.1x=.2(2+x) | | 2(b+5)+6b=5b+2b+1 | | 4x-13x+10=0 |